Adherence to the 4S-AF Scheme in the Balkan region: insights from the BALKAN-AF survey. (14th October 2021) - Koziel, M; Mihajlovic, M; Nedeljkovic, M; Pavlovic, N; Paparisto, V; Music, L; Trendafilova, E; Rodica Dan, A; Kusljugic, Z; Dan, G.-A; Lip, G; Potpara, T; et al.
Abstract: Background: Current European Society of Cardiology guidelines on atrial fibrillation (AF) propose a structured characterization of AF in order to facilitate the evaluation of patients by physicians at all healthcare levels. The 4S-AF structured scheme includes four domains: stroke risk, symptoms, severity of AF burden and substrate severity. Purpose: To evaluate the adherence to the 4S-AF scheme in patients with high risk of stroke (CHA2DS2-VASc score ≥3 in females or ≥2 in males) in the post-hoc analysis of the BALKAN-AF dataset. Methods: Prospective enrolment of consecutive patients with electrocardiographically documented AF was conducted in seven Balkan countries. Results: Of the 2, 712 enrolled patients, 2, 712 (100.0%) had data on CHA2DS2-VASc score. 162 (6.0%) had truly low risk of stroke (CHA2DS2-VASc score of 0 in males and 1 in females). 2099 (77.4%) of patients had high risk of stroke and 613 (22.6%) individuals had low or intermediate risk of stroke (CHA2DS2-VASc score <3 in females or <2 in males). 75 (46.3%) of patients with truly low stroke risk and 1555 (74.1%) of patients with high risk of stroke were offered oral anticoagulants (OAC). Of the 2, 712 patients, 2, 677 (98.7%) had data on European Heart Rhythm Association (EHRA) symptom score. Among 2, 099 patients with high risk of stroke, 703 (33.4%) individuals had EHRA symptom score of 3 or 4. 207 (29.4%) of patients with EHRA symptom score of 3 or 4 and high risk of stroke were offered rhythm control strategy. 620 (55.2%) of patients with first diagnosed AF or paroxysmal AF with high risk of stroke were offered rhythm control strategy. 1927 (91.8%) of patients with high risk of stroke had ≥2 comorbidities. Mean left atrial diameter in patients with high risk of stroke was 46.5±7.8 mm. Conclusions: OAC overuse was seen in patients with truly low stroke risk, whist OAC underuse was evident in patients with high risk of stroke. The proportion of highly symptomatic patients (EHRA 3 or 4) with high risk of stroke who were offered rhythm control strategy was low. The proportion of patients with first diagnosed AF or paroxysmal AF with high risk of stroke who received rhythm control was small. The majority of AF patients with high risk of stroke had ≥2 comorbidities. Overall, treatment decision-making was not based on the 4S-AF scheme. Funding Acknowledgement: Type of funding sources: None.